A model for implementing sustainable tourism in mangrove ecotourism at Batu Lumbang, Pemogan Village, Bali - Swariga, I Made; Anggara, Bagas; Raditia, I Gede Agus (Bali Tourism Journal, 2025)
Abstract: The Batu Lumbang Mangrove Ecotourism area in Pemogan Village, Bali, demonstrates a successful transformation from a degraded coastal zone into a sustainable tourism destination through active collaboration among local communities, government agencies, and private sector partners. This study employs a qualitative case study approach, utilizing participatory observation and in-depth interviews to examine the implementation of sustainable tourism and the roles of key stakeholders. The findings reveal that community-led conservation efforts, environmental education-based attractions, and the development of eco-friendly mangrove-based products—such as syrup, sticks, tea, and eco-print batik—have significantly contributed to ecological restoration and local economic development. The integration of traditional knowledge, inclusive participation, and shared resource management forms the foundation of sustainability practices in this site. This model offers valuable insights for the development of community-based coastal ecotourism in other regions.